Factors contributing to lower than expected recovery rates of HIV negative children on the therapeutic feeding program - Gudyanga, Ephias; Gudyanga, Nyashadzashe Sharon; Gudyanga, Anna; Tshalibe, Ropafadzo S. (Science Publishing Group, 2016)
The study sought to find out factors contributing to lower than expected recovery rates of HIV negative children on the therapeutic feeding program. Qualitative design was employed. Twenty (20) caregivers were interviewed at Gweru District Health Offices in Zimbabwe. Findings indicated that socio-economic factors, level of education and caring practices of the caregiver and the cultural practices to a larger extent contributed to the lower than expected recovery rates of HIV negative children on the therapeutic feeding program. Epi Info, used as database software showed that the exposure variables had an association with the outcome (recovery). Stunted children had 89% less chances of recovering, breast feeding children had 83% more chances of recovering unlike those not breast fed. Socio demographic factors had more impact on the recovery of the child. The Zimbabwean government should spend more money on quality nutritional programs to improve the state of malnutrition. More nutrition campaign is inevitable in an effort to promote health.